Social Value Creation and Institution-Entrepreneurial Dynamics in a Three Sector Economy - Dafuleya, Gift (Journal of Economics and Behavioral Studies, 2014)
This paper attempts to answer the question: who creates social value in an economy, for whom and how? By examining the focal institutions that operate in a three sector economy, the paper, at the risk of oversimplifying and over narrowing the scope, develops an institution-entrepreneurial matrix that categorise institutions and provides clarity on the field of play. Coupling this with an institutions-actions model, the paper creates two scenarios of institution-entrepreneurial dynamics within the context of social value creation. The analysis demonstrate that mission drifts that adjust the realm of organizations are inevitable, but need to be carefully managed to avoid mix-up on who does what, for whom and how. At the heart of the discussion is the role of social entrepreneurs whose creation of social value to the segment of humanity in an unjust equilibrium is slightly distinct from the rest. Their unique realm lies in the realisation of nuanced pare to improvements.